Javanese language and cultural identity: The role of ritual speech in traditional ceremonies of Solo city - Zanah, Sri Wahyuni Samaratul (TALENTA, 2025)
Fieldwork in Solo shows that Krama Inggil remains widely used in traditional ceremonies, such as Kirab Pusaka and Tedhak Siten, where formal Javanese creates a solemn and culturally rich atmosphere. Ritual speech is often formulaic, poetic, and passed down orally, reflecting core Javanese values like respect, obedience, and humility. Community members view ceremonial language as a symbol of dignity and ancestral honor. However, there is a growing intergenerational gap: many young people can recite ritual texts but do not understand their meaning, reflecting a decline in functional competence. This aligns with Fishman’s theory that language used solely for ceremonial purposes is vulnerable to shift. Despite this, rituals still function as important sites of language preservation and cultural resistance. Events like Sekaten expose younger generations to classical Javanese, and community initiatives help children learn and appreciate traditional forms such as tembang macapat. Challenges include limited daily use of Javanese, reliance on rote learning in schools, and the commercialization of ceremonies, which sometimes replaces Krama with Indonesian. To preserve linguistic and cultural heritage in Solo, broader efforts are needed to integrate Javanese into homes, education, media, and intergenerational interaction.